Chitosan as an antimicrobial agent for footwear leather components - Barros, M.C. (2012)
Chitosan is being increasingly used in distinct areas such as pharmaceutical, biomedical, cosmetics, food processing and agriculture. Among the interesting biological activities that have been ascribed to chitosan, the antimicrobial activity is probably the one to generate the higher number of applications. Within this work the role of chitosan in diverse applications has been reviewed with particular emphasis for those exploring its antimicrobial power. Furthermore, the mechanism to explain the antimicrobial activity of this emerging biopolymer is also discussed. The viability of using chitosan to effectively provide a functional coating for leather products was presented through an experimental case study. Results confirmed the potential of using this strategy to create antimicrobial leather products to be used, e.g., in the footwear industry.